The Profil Berpikir Relasional Siswa SMP dalam Memecahkan Masalah Aljabar Ditinjau dari Kemampuan Matematika - Mia Saskia; Budayasa, I Ketut; Manuharawati, Manuharawati (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2023)
This research aims to describe the profile of junior high school students' relational thinking in solving algebraic problems viewed from mathematical ability. In this qualitative research, data collection techniques were tests and interviews. The subjects of this research consisted of 3 (three) Grade 8th-G students of SMPN 1 Taman with low, medium, and high math skills of the same gender. The problem-solving step uses Polya's problem-solving stages. The results showed that students with medium and high mathematical abilities think relationally up to the looking back stage. While students with low mathematical ability is limited up to the stage of carrying out the plan. The subjects use previous knowledge related to algebra, especially linear equations and inequalities for two variables, to relate problems information and solving strategies.